The Impact of COVID-19 Fiscal Policy on the Performance of Slovak State Budget in 2020 and 2021 - Gdovcova, Zuzana; Menzl, Vojtech (Ekonomický časopis/Journal of Economics, 2025)
The contribution deals with the Slovak fiscal and budgetary policy as implemented and carried out during and immediately after the initial outburst of the COVID-19 pandemic. Its primary aim is to test the existence of the impact of the pandemic on fiscal developments and to quantify it using the estimate of the overall cash-based performance of the State budget of the Slovak Republic in 2020 and 2021. Next, the paper sets out to analyse the degree of disruption to the Slovak public finances due to the expansive fiscal policy measures aimed at mitigating the pandemic effects in 2020 and 2021 (i.e. stabilising macroeconomic variables). Deviances in the current performance of the Slovak State budget are assessed using the combination of actual values and own forecasts (point estimates), the latter being sourced from the authorial SARIMA-based econometric models applied on the 2010 – 2019 quarterly time series of the Slovak Republic’s State budget cash revenues and expenditures. Particular attention is paid to the associated additional expenditures and/or reduced (missing) budgetary revenues.